THE EFFECT OF PROPOLIS ON HISTOPATHOLOGICAL OBSERVATION IN WHITE RAT’S KIDNEY GIVEN HIGH DOSE OF PARACETAMOL - Febilani, Elti; Berata, I Ketut; Samsuri, Samsuri; Merdana, I Made; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2017)
The purpose of this study is to determine the effect of propolis on kidney histopathological representation of white rats were given the toxic dose paracetamol. 25 male rats males were used in this study who were divided into 5 groups, control group (P0) without treatment, group 1 (P1) that was given paracetamol doses 250mg/kg, group 2 (P2), group 3 (P3), and group 4 (P4), given paracetamol dose of 250mg / kg and propolis added 0.25 ml (P2), 0.50 ml (P3), and 0.75 ml (P4). Paracetamol and propolis were given orally by mixing it into the water provided ad libitum for 10 days. Then performed a necropsy and kidney  were taken aseptically for making of histopathology preparations with hematoxylin eosin (HE) staining. The examined variables were fatty degeneration and necrosis in the proximal tubules of the kidney. Results indicate that fatty degeneration and necrosis were showed in treatment P1, while the entire treatment P2, P3, and P4 show the repair from the damage caused by the paracetamol. Treatment P4 gives the best results in reducing the effects of the paracetamol. Kruskal-Wallis showed a significant difference from fatty degeneration and necrosis of the tested group. From this study it can be concluded that the propolis with dose 0.75 ml giving better protection than 0.25 ml and 0.50 ml dose.
Keywords: Kata kunci: Parasetamol; propolis; radikal bebas; antioksidan; ginjal